Practice as research: Approaches to creative arts enquiry - Barrett, Estelle; Bolt, Barbara (New York I.B.Tauris, 2007)
Practice-led research is a burgeoning area across the creative arts, with studio-based doctorates frequently favoured over traditional research. Yet until now there has been little published guidance for students embarking on such research. This is the first book designed specifically as a pedagogical tool and is structured on the model used by most research programmes. A comprehensive introduction lays out the book's framework and individual chapters provide concrete examples of studio-based research in art, film and video, creative writing and dance, each contextualised by a theoretical essay and complete with references. More than a handbook, the volume draws on thinkers including Deleuze, Bourdieu and Heidegger in its examination of the relationship between practice and theory, demonstrating how practice can operate as a valid alternative mode of enquiry to traditional scholarly research. Taking pains to elaborate methodologies, contexts and outcomes, and emphasising the process of enquiry and its relationship to the research write-up or exegesis, this is an indispensable tool for educators and students.